Baicalein Mediates Mitochondrial Autophagy via miR-30b and the NIX/BNIP3 Signaling Pathway in Parkinson's Disease. (19th August 2021) - Chen, Min; Peng, Li; Gong, Ping; Zheng, Xiaoli; Sun, Tao; Zhang, Xiaoqiao; Huo, Jiangtao
Abstract : Parkinson's disease (PD) is regarded as a severe neurodegenerative disorder. Baicalein is involved in the treatment of PD. This study explored the mechanism of baicalein in PD. The PD rat model was established using 6-hydroxydopamine. The neurologic score, dopamine (DA) content, apoptotic cells, and neuronal damage were evaluated after rats were treated with baicalein. Autophagy in PD rats was inhibited using 3-methyladenine (3-MA). The mitochondrial membrane potential (MMP) and autophagy-related proteins (LC3, P62) were detected. Next, agomiR-30b was transfected into PD rats. The targeting relation between miR-30b and NIX was predicted and verified. Then, sh-NIX was transfected into PD rats, and the effects of miR-30b and NIX on MMP, LC3, and P62 were assessed. When miR-30b was overexpressed using agomiR-30b, the NIX and BNIP3 levels were detected. Baicalein increased the neurological score and restored DA content, neurons, MMP, and mitochondrial autophagy protein levels. Baicalein inhibited miR-30b expression and miR-30b targeted NIX. miR-30b upregulation or NIX silencing reversed the effect of baicalein on MMP and mitochondrial autophagy. Baicalein upregulated NIX and BNIP3 expressions, while miR-30b overexpression inhibited NIX and BNIP3 expressions. In summary, baicalein mediated mitochondrial autophagy and restored neuronal activity by downregulating miR-30b and activating the NIX/BNIP3 pathway, thus protecting against PD.